Ophiorrhiza pseudonapoensis (Rubiaceae), a new species from Yunnan, southwestern China - Liu, Qin; Chen, Ao-Xue; Liao, Xiao-Wen; Liu, Quan-Ru; Wu, Lei (Phytotaxa, 2023)
Ophiorrhiza pseudonapoensis, a new species of Rubiaceae is described and illustrated from China. It was previously confused with O. napoensis but differs from the latter in having 5–10 (vs ca. 1) mm long and persistent (vs caducous) stipules, oblanceolate bracts (vs lanceolate-linear), monostylous (vs heterostylous) flowers, and ensiform (vs narrowly triangular) calyx lobes. Ophiorrhiza pseudonapoensis is also morphologically similar to O. macrocarpa, but can be distinguished from the latter by its 5–10 (vs less than 1) mm long stipules, oblanceolate (vs subulate or linear subulate) and 7–20 (vs less than 5) mm long bracts, and (1.2–)1.5–2(–2.5) (vs 0.4–0.6) mm long calyx lobes. The conservation status was assessed as Least Concern (LC) according to the IUCN Red List categories and criteria.